Altered Frequency and Phenotype of HLA-G-Expressing DC-10 in Type 1 Diabetes Patients at Onset and in Subjects at Risk to Develop the Disease - Amodio, Giada; Mandelli, Alessandra; Curto, Rosalia; Rancoita, Paola M. V.; Stabilini, Angela; Bonfanti, Riccardo; de Pellegrin, Maurizio; Bosi, Emanuele; Di Serio, Clelia; Battaglia, Manuela; Gregori, Silvia (Frontiers in Immunology, 2021)
Type 1 diabetes (T1D) is a chronic autoimmune disease resulting in progressive destruction of b-cells. Several factors affecting lymphocyte activities and antigen-presenting cells, including dendritic cells (DC) contribute to defective maintenance of tolerance in T1D. DC-10 are a subset of human DC involved in IL-10-mediated tolerance. A precise monitoring of DC-10 in the peripheral blood is possible thank to the discovery of specific biomarkers. DC-10, being cells that naturally express HLA-G, may be used for the appropriate staging of the disease. By enumerating and phenotypically characterizing DC-10 in peripheral blood of subjects at different stage of T1D development: first-degree relatives (FDR) of T1D patients, without (Abneg) or with (Abpos) autoantibodies, T1D patients at onset, and age-matched healthy controls (HC), we showed that DC-10 contain a high proportion of HLA-G-expressing cells compared to monocytes. We reported that low frequency of DC-10 during disease development is paralleled with the increased proportion of pro-inflammatory cDC2 cells. Moreover, DC-10 number and phenotype differ from Abneg FDRs, Abpos FDRs, and T1D patients compared to HC, and DC-10 from T1D patients express low levels of CD83. Finally, multiple regression analysis, considering DC-10 and HLA-G-related parameters, showed that Abneg FDRs are more similar to subjects with autoimmunity than to HC. This is the first demonstration that impairment in DC-10 number and phenotype, specifically CD83 expression, is associated with risk of developing T1D, suggesting a possible use of CD83+ DC-10 to stratify individuals at risk of T1D in conjunction with classical prognostic factors.